(untitled) (Research, Society and Development, 2020)
During COVID-19’s confrontation of the pandemic, it was necessary to adopt alternative measures in the political-educational context in order to maintain the school year. The objective of the study was to present the measures deliberated by the political sector in the educational area during the pandemic and to reflect the social impact of these measures in professional and technological education. In this qualitative review, the articles, published in 2020, were selected from the Scielo and Google Scholar databases. After reviewing the measures deliberated by the political-educational sector, it was noted that these were based on a general model, without considering the difficulties of access and the quality of education to be offered. Public education institutions signaled that a portion of students do not have access to the internet, which directly impacts access to quality education and increasing dropout rates. It is noted that the federal educational institutions have developed internal mechanisms to include students without access to the internet. However, the lack of access to computers and the internet by public school students has been a problem since before the pandemic. The political and social relationship in the educational context is complex. Efforts are being made by the school community to democratize education for all students during the pandemic period. We suggest that for better applicability of remote education during the pandemic, more investments should be made by government agencies in order to provide access to all EPT students and reduce dropout rates and social inequalities.